PENGARUH PELATIHAN DAN MOTIVASI TERHADAP PENGEMBANGAN KELOMPOK TANI (MEKAR) DI DESA PALESANGGAR KECAMATAN PEGANTENAN - Fitrianti, Rani Nur; Rahayu, Runik Puji; Habibi, Nur Syakherul (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2023)
The existence of farmer groups still cannot be a solution to create change in Palesanggar Village. The purpose of this study was to see the effect of training and motivation on the development of farmer groups in Palesanggar Village, Pegantenan District. This study uses an associative research method with multiple linear regression as a means of analysis. The sampling technique was carried out by means of total sampling or saturated samples, a total sample of 74 farmers. The results showed that training and motivation had a significant effect on the development of farmer groups in Palesanggar Village, Pegantenan District. Training is the variable that has the most significant influence on the development of farmer groups. Therefore, members of farmer groups should be motivated to take part in activities held by agricultural extension workers in farmer groups because it can increase farming knowledge, attitudes and skills.